Does prehospital spinal immobilization influence in hospital decision to obtain imaging after trauma?. Issue 4 (April 2020) - Drain, Joseph; Wilson, Eleanor S.; Moore, Timothy A.; Vallier, Heather A.
Highlights: Trauma patients were more likely to undergo cervical spine imaging if they arrived to the emergency department wearing a cervical collar. Proven clinical assessments to assess a cervical spine are sufficient to eliminate need for cervical CT imaging. Proven clinical assessment methods may reduce excessive use of hospital imaging resources, finances, and time. Abstract: Importance: : This study highlights the unnecessarily high suspicion for cervical spine injury among study providers and shows that cervical CT scans were more likely in patients who arrived to the emergency department wearing a cervical collar, even when clinically cleared for suspicion of cervical spine injury by the emergency department provider. Objective: : To determine if patients with a cervical collar were more likely to undergo cervical spine imaging than those who arrived to the emergency department without a collar. Design: : Adult trauma patients at a level 1 trauma center over 4 months (n = 1, 438) were stratified by acuity (1, 2, or 3), mechanism, and known injury cephalad to clavicles, defined as pain, wounds, or hematomas. Cervical spine imaging findings were recorded. Results: : 975 patients (67.8%) had cervical CT scans. Twenty-six (1.81%) sustained a fracture or ligamentous injury, all with known injury cephalad to clavicles. 161 (11.2%) patients without injury cephalad to clavicles all had a negative cervical CT. Category 1 patients with gunshot wounds with injury cephalad to clavicles were more likely to have CT if they arrived with a collar versus without (66.7% vs 14.3%, p = 0.027). Category 2 and 3 patients with injury cephalad to clavicles after motor vehicle collision (MVC) (88.2% vs 69.6%, p = 0.011), low energy falls (88.3% vs 59.4%, p < 0.0001), and assault (86.0% vs 37.1%, p < 0.0001) underwent cervical CT more frequently if they arrived wearing a collar. Category 2 and 3 trauma patients without injury cephalad to clavicles were also more likely to undergo CT when wearing a collar after MVC (66.3% vs 21.4%, p = 0.001), low energy fall (81.8% vs 35.3%, p = 0.016), and pedestrian vs MVC (55.6% vs 12.5%, p = 0.04). Conclusion: : Certain trauma patients were more likely to undergo cervical CT if they arrived wearing a cervical collar. No conscious patients without complaints proximal to the clavicles had cervical injury.